The function given is:
![y=2e^(-x)](https://img.qammunity.org/2023/formulas/mathematics/college/8aegrkd3498t4nje2r5w95dldm6bbwo5lx.png)
(a)
The function represents exponential decay. An exponential decay describes the process of reducing an amount by a consistent percentage rate over a period of time. We can re-write the equation as:
![\begin{gathered} y\text{ = }2e^(-x) \\ y\text{ = 2 }* e^(-x) \\ y\text{ = 2 }*\text{ }(1)/(e^x) \\ =\text{ }(2)/(e^x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x4u3z2tkjoxfup1spbws25gu334facjedx.png)
Recall that by law of indices:
![a^(-1)\text{ = }(1)/(a)](https://img.qammunity.org/2023/formulas/mathematics/college/7fdlubapupsz5o0rdiztke3t9frjk75vby.png)
As x grows large, the value of y decreases and approaches zero.
(b) The graph of the function is shown below.